Nutritive Value and Preference of Guinea-Grass Ensiled with or without Additive by West African Dwarf (WAD) Goats - T. O. Abegunde; S. O. Babalola; B. T. Adeoye; A. O. Usman; O. M. Akinyemi (Tropical Animal Science Journal, 2021)
A study was designed to investigate silage additives’ effect on preference and nutritive value of five weeks re-growth guinea grass by West African dwarf (WAD) goats. The silages of five weeks re-growth guinea grass were made without additive (T1), with cassava peels additive (T2), and with fermented epiphytic juice of lactic acid bacteria in Panicum maximum (FEJPM) additive (T3). The effects of silage additives on preference, voluntary feed intake, growth, digestibility, and nitrogen utilization were assessed using 18 growing WAD goats (BW: 5.88±0.26 kg) in a completely randomized design. Dry matter was significantly (p<0.05) higher in T2 silage (40.70 g/100g) than in T1 silage (39.00) and T3 silage (34.60). Crude protein values were similar (p>0.05) in T1 and T3 silages (10.63 and 10.72 g/100g DM) that were significantly lower (p<0.05) than that in T2 silage (12.54 g/100g DM). The silages of guinea grass had acceptable physical attributes in terms of color, odor, and texture, with pH values ranging from 3.87- 4.97. T1 and T3 silages were rejected, whereas T2 silage was accepted well by the experimental WAD goats. Average daily feed intake (ADFI) was significantly (p<0.05) the highest in the WAD goats fed T2 silage (303.30 g/day), and the lowest (p<0.05) was found in WAD goats fed T1 silage (271.60 g/day). Similar to the ADFI, the highest average daily gain (ADG) was found in WAD goats fed T2 silage (37.25 g/day), and the lowest ADG (p<0.05) was found in WAD goats fed T1 silage (24.50 g/day). Feed conversion ratio (FCR) of WAD goats fed T2 silage (8.15) was superior to those of WAD goats fed T1 silage (13.63) and T3 silage (9.66). Crude protein and dry matter digestibility values were higher (p<0.05) in WAD goat fed T2 silage (68.24 and 63.87%, respectively) than in WAD goats fed T1 and T3 silages. Nitrogen intake and balance were significantly (p<0.05) the highest in WAD goats fed T2 silage (12.41 and 8.68 g/day, respectively), and these variables were similar in WAD goats fed T1 and T3 silages. Nitrogen retention was not affected by the silage additives. It was concluded that cassava peels were better than FEJPM as a silage additive since it improved fermentative quality, acceptability, feed intake, and digestibility of guinea grass silage by WAD goats.